Making programmes worth their salt: Assessing the context, fidelity and outcomes of implementation of the double fortified salt programme in Uttar Pradesh, India - Shruthi Cyriac; Amy Webb Girard; Usha Ramakrishnan; M. G. Venkatesh Mannar; Kriti Khurana; Rahul Rawat; Lynnette M. Neufeld; Reynaldo Martorell; Mduduzi N. N. Mbuya (Wiley, 2022)
Abstract Double fortified salt (DFS) has proven efficacy in addressing iron deficiency and anaemia, thus improving maternal and child nutrition outcomes. However, DFS delivery in large‐scale settings is less understood, with limited documentation of its fidelity of implementation (FOI). We assessed the FOI of the DFS intervention in Uttar Pradesh, India, to improve the design and implementation of such programmes that aim to reduce the anaemia burden, especially in women of reproductive age (WRA). We conducted in‐depth interviews with DFS programme staff (n = 25) and end‐user WRAs (23), guided by a programme impact pathway. We transcribed and thematically analysed the interviews and used an adapted analytic framework to document FOI across four domains-objects of intervention, implementation staff, implementation context and target of implementation. DFS utilisation remained low due to a combination of factors including poor product quality, distribution challenges, ineffective promotion and low awareness amongst end‐user WRAs. Motivation levels were higher amongst district‐level staff compared to frontline staff, who lacked supervisory support and effective incentives to promote DFS. Three typologies of DFS users emerged-'believers', 'thrifters' and 'naysayers'-who indicated differing reasons for DFS purchase and its use or nonuse. The implementation of the DFS programme varied significantly from its theorised programme impact pathway. The adapted analytic framework helped document FOI and assess the programme's readiness for impact assessments and subsequent scale‐up. The programme needs product quality improvements, incentivised distribution and stronger promotion to effectively deliver and improve the realisation of its potential as an anaemia prevention strategy.